Mechanisms of root exudates and soil microbial responses to nitrogen reduction and companion cropping for tomato yield increase and quality improvement - Liu, Deyang; He, Xingjia; Liu, Yingxue; Sun, Chaofan; Su, Chunjie; Lang, Yishan; Wu, Xia (Frontiers in Plant Science, 2025)
The utilization of nitrogen fertilizer in excess over an extended period in facility cultivation has been demonstrated to engender a decline in tomato yield and quality, thus becoming a bottleneck issue that restricts production. In order to explore the biological mechanisms of nitrogen reduction and companion planting patterns on tomato yield and quality, this study conducted a two-year pot experiment under different nitrogen application levels and planting patterns, multisystem analysis of tomato rhizosphere soil microbial communities and root secretions was performed using 16S Illumina MiSeq sequencing and LC-MS/MS mass spectrometry. Over two years, the yield of tomatoes grown using reduced nitrogen and companion planting increased by 34.26% and 35.54% compared to monoculture, and by 1.23% and 3.57% compared to the application of conventional nitrogen and companion planting. Nitrogen use efficiency increased by 9.81% and 11.36%, respectively. The nitrogen reduction and companion planting model increased the content of soluble sugars and lycopene, improved soil dehydrogenase and protease activity, and changed the composition of rhizosphere bacterial communities and root exudates. At all nitrogen application rates, companion planting increased the abundance of Pseudomonas. In the 30% nitrogen reduction and conventional nitrogen application systems, the abundance of differential metabolites such as methionine and pipecolic acid was significantly higher in companion crops than in tomato monoculture. On the other side, soil bacteria and root exudates form a complex network of interactions, in which rhizosphere bacteria such as MND1 are positively correlated with Sphingomonas. In summary, the cultivation model of nitrogen reduction and companion planting of potato onions changed the composition of the tomato soil bacterial community and the metabolic pathways of root exudates, enhanced the activity of nitrogen conversion-related enzymes, and promoted the absorption and utilization of nitrogen nutrients by tomatoes, which provides a theoretical basis for increasing the yield and quality of tomatoes cultivated with 30% nitrogen reduction and companion planting of onions.